The implications of horizontal inequality for aid - Graham Brown; Frances Stewart; Arnim Langer (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
This paper argues that the reduction of horizontal inequalities (HIs) or inequalities between culturally defined groups should inform aid policy in heterogeneous countries with severe HIs. It shows how this would change aid allocation across countries, leading to more aid to heterogeneous countries relative to homogeneous ones, the opposite of the existing bias in aid distribution. It explores how adopting an HI approach would affect the use of particular aid instruments, arguing that different instruments are appropriate according to the attitude and capacity of the government in relation to correcting HIs. Drawing on case studies of Ghana and Nepal it argues that at present there is neglect of HI considerations in aid policy, which can be particularly damaging where aid forms a large part of government resources.
Keywords: F35; D63; 330; aid; horizontal inequality; social exclusion; Nepal; Ghana; Soziale Gerechtigkeit; Soziale Isolation; Entwicklungshilfe; Nepal; Ghana